Case Report: Treatment of Anti-MDA5-Positive Amyopathic Dermatomyositis Accompanied by a Rapidly Progressive Interstitial Lung Diseases With Methylprednisolone Pulse Therapy Combined With Cyclosporine A and Hydroxychloroquine - Zhang, Qia-Chun; Liu, Min-Ying; Chen, Zhi-Xin; Chen, Yimin Talia; Lin, Chang-Song; Xu, Qiang (Frontiers in Medicine, 2020)
Introduction: Patients with anti-MDA5 antibody-positive Amyopathic dermatomyositis (ADM) often develop rapidly progressive interstitial lung diseases (RP-ILD), with poor treatment success. Many studies have shown that this is the main cause of death in patients with anti-MDA5 antibody positive ADM. Case presentation: A 37-year-old woman presented with cough, shortness of breath and a rash on both hands that resembled Gottron's signs. Upon laboratory examination the following results were obtained: ANA positive; anti-Ro52 antibody strongly positive; anti-MDA5 antibody positive. Pulmonary HRCT scan showed pulmonary interstitial inflammatory changes, mediastinal and subcutaneous emphysema. She was finally diagnosed with anti-MDA5 antibody-positive ADM accompanied by RP-ILD. She was first given high dose steroid pulse therapy with methylprednisolone (500mg, per day for 3 days) followed by methylprednisolone (40mg, daily), cyclosporine A (100mg, twice per day) and hydroxychloroquine (200mg, twice per day). Since her discharge from our hospital in March of 2018, she has maintained the methylprednisolone therapy (tapered to 10mg daily), cyclosporine A (100mg, twice per day) and hydroxychloroquine (200mg, twice per day). Outcomes: Pulmonary HRCT scans taken 03 August 2018, 17 December 2018 and 17 May 2020 showed that the interstitial pneumonitis had significantly improved, and mediastinal and subcutaneous emphysema had been gradually absorbed. The patient can now participate in normal work and activities of daily living. Conclusion: The treatment of methylprednisolone pulse therapy combined with cyclosporine A and hydroxychloroquine may be an option for the RP-ILD accompanied by anti-MDA Positive ADM. After the acute phase, this combination therapy strategy is helpful to the disease control of patients.